Pengaruh Kualitas Pelayanan Housekeeping Department Terhadap Tingkat Kepuasan Tamu Menginap Di Hotel Santika Premiere Harapan Indah Bekasi - Niken Utami Wahyu; Mulyati; Maya Oktaviani (Journal of Mandalika Review, 2022)
This study aims to determine the Influence of the Quality of Service of the Housekeeping Department To the Satisfaction Level of the Guests Staying at Hotel Santika Premiere Harapan Indah Bekasi. Data collection method survey approach with correlational. The population in this study is a hotel with a total sample of 80 respondents consisting of male and female. Determination of the sample in this study using the slovin formula with data collection Techniques using a questionnaire (questionnaire) quality of service of the housekeeping department and the level of satisfaction of the guests. Hypothesis test data were analyzed by simple linear regression. The results of the calculation of the correlation coefficient values obtained rhitung is by 0,673> rtabel is of 0.220, it can be concluded that there is a correlation between the variables of service quality and guest satisfaction. The next known value Sig. (2-talled) between service quality and guest satisfaction is of 0.000 < 0.05, which means there is a significant correlation between the quality of service of the housekeeping department with the level of satisfaction of the guests staying at Hotel Santika Premiere Harapan Indah Bekasi. Implications the results of this study that there is a positive relationship between the quality of service of the Housekeeping Department to the satisfaction level of the guests staying at Hotel Santika Premiere Harapan Indah Bekasi. The application of quality Housekeeping service can provide a strong influence on the satisfaction of the guests staying at the hotel that the implementation of the duties and responsibilities of Housekeeping Department in Hotel Santika Premiere Harapan Indah Bekasi implemented properly and done with attention to standard operating pocedur (SOP).